Assement of styloid process length in orthopantomogram - a radiographic study - DIVYADHARSHINI; JAYANTH KUMAR V (International Journal of Pharma and Bio Sciences, 2016)
Styloid process is a process or projection from the skull base with a normal length of 2.5-3.0 cm. In certain individuals for a variety of reasons there may be an elongation of styloid process. Abnormally long styloid process becomes symptomatic in patients and manifest as Eagle’s Syndrome. The aim of our study was to retrospectively measure the length of the styloid process on archived Orthopantomograms(OPG). This study was carried out in the Department of Oral Medicine & Radiology, Saveetha Dental College, Chennai. In this study a total of 132 OPG’s were included into the study. After a preliminary assessment 32 OPG’s were excluded for dimensional distortions and 100 were taken for the final assessment. This sample had a composition of 53 males and 47 females. The mean length of males right and left styloid process was 3.34 cm±0.69 and 2.95 cm±0.62 respectively. The mean length of female right and left styloid process was 3.35 cm±0.77 and 3.05cm ±0.76 respectively.This study revealed that the length of the styloid process on the right side was higher than the average and the left side was normal within limits.